Improving The Student Listening Skills through Hello English Application - Cut Ria Manisha; Santoso, Didik (ITScience (Information Technology and Science), 2025)
This study examines the effectiveness of the Hello English app in improving the English listening skills of ninth-grade students at Subulussalam Junior High School. Using Coats' (2005) model in two research cycles, this classroom action research involved 23 students. The impetus for this research arose from the challenges students continuously faced when trying to understand spoken English. These challenges include fast audio speed, unfamiliar vocabulary, and difficulty concentrating during listening activities. Quantitative data collected during the study showed a significant improvement in students' listening scores, with the average score increasing significantly from 45.1 before the intervention to 83.4 afterward. This improvement can be attributed to students' increased familiarity with the interactive features of the Hello English app. These features include repetition options, feedback, audio level adjustment, and engaging gamified learning elements. Qualitative data from interviews with students and teachers highlight a significant increase in students' engagement levels, motivation, and self-confidence from using the app. The findings of this study indicate that the Hello English app effectively improves listening skills. This is achieved by promoting active and independent learning, which aligns with metacognitive strategies and gamification principles. By fostering a sense of independence and creating a student-centered learning environment, this study concludes that integrating digital applications in language teaching not only addresses common listening challenges but also supports the objectives of the Merdeka Belajar curriculum.